我发现即使使用了提示词,在使用 GitHub Copilot 的网页版时,行内公式仍然无法正确显示。
一些行内公式被正确地包裹在单个 $ 中,因此公式可以正确显示,但大多数行内公式都被错误地包裹在两个 $$ 中,导致公式无法正确显示。
GitHub Copilot 网页版的链接是 https://github.com/copilot
我使用的模型版本是 o3-mini。
我应该使用什么提示词才能正确显示公式,或者这是否是 GitHub Copilot Web 的内部问题?
下面是我使用的个人指令。
Please use the correct LaTeX math formula formatting in your responses:
1. Inline formulas: Use single dollar signs, for example $E=mc^2$
2. Display formulas: Use double dollar signs
下面是一个例子。你可以看到一些行内公式被错误地用两个美元符号括起来,所以它们没有被正确显示。
The Leibniz criterion (or alternating series test) states that an alternating series
$$
\sum_{n=1}^{\infty} (-1)^{n-1} a_n,
$$
converges if the sequence $(a_n)$ satisfies the following two conditions:
1. The sequence is monotonically decreasing:
$$
a_1 \ge a_2 \ge a_3 \ge \cdots \ge 0,
$$
2. The terms converge to zero:
$$
\lim_{n\to\infty} a_n = 0.
$$
Below is a classical proof of the criterion.
---
**Proof:**
Define the \( n \)th partial sum of the series by
$$
s_n = \sum_{k=1}^n (-1)^{k-1} a_k.
$$
We will show that the sequence \( (s_n) \) converges by demonstrating that the partial sums form two sequences—one consisting of the even-indexed partial sums and one consisting of the odd-indexed partial sums—that are monotonic and bounded, and that they “squeeze” the series into a unique limit.
1. **Consider the subsequence of odd-indexed partial sums:**
Let
$$
s_{2n-1} = a_1 - a_2 + a_3 - \cdots + a_{2n-1}.
$$
To see that \( (s_{2n-1}) \) is decreasing, observe that
$$
s_{2n-1} - s_{2n+1} = \Big[a_1 - a_2 + \cdots + a_{2n-1}\Big] - \Big[a_1 - a_2 + \cdots + a_{2n-1} - a_{2n} + a_{2n+1}\Big].
$$
This simplifies to
$$
s_{2n-1} - s_{2n+1} = a_{2n} - a_{2n+1}.
$$
Since \( a_{2n} \ge a_{2n+1} \) (by the monotonicity assumption), we have
$$
s_{2n-1} \ge s_{2n+1}.
$$
Thus, the odd-indexed partial sums form a decreasing sequence.
2. **Consider the subsequence of even-indexed partial sums:**
Let
$$
s_{2n} = a_1 - a_2 + a_3 - \cdots - a_{2n}.
$$
Now, compare consecutive even-indexed partial sums:
$$
s_{2n+2} - s_{2n} = \Big[s_{2n} - a_{2n+1} + a_{2n+2}\Big] - s_{2n} = - a_{2n+1} + a_{2n+2}.
$$
Because \( a_{2n+1} \ge a_{2n+2} \), it follows that
$$
- a_{2n+1} + a_{2n+2} \ge 0,
$$
so
$$
s_{2n+2} \ge s_{2n}.
$$
Therefore, the even-indexed partial sums form an increasing sequence.
3. **Bounding the two subsequences:**
Notice that for every \( n \),
$$
s_{2n} \le s_{2n-1}.
$$
This is because \( s_{2n-1} = s_{2n} + a_{2n} \) and \( a_{2n} \ge 0 \).
Consequently, the entire sequence of partial sums is "squeezed" between these two subsequences:
- The increasing sequence \( (s_{2n}) \) is bounded above by \( s_1 \) (since \( s_1 \) is the first odd partial sum).
- The decreasing sequence \( (s_{2n-1}) \) is bounded below by \( s_{2n} \).
By the Monotone Convergence Theorem, both sequences converge; denote
$$
\lim_{n\to\infty} s_{2n} = L \quad \text{and} \quad \lim_{n\to\infty} s_{2n-1} = M.
$$
Since
$$
s_{2n} \le s_{2n-1}
$$
for all \( n \) and the difference between them is \( s_{2n-1} - s_{2n} = a_{2n} \), which tends to 0 by assumption, we obtain
$$
\lim_{n\to\infty} \big(s_{2n-1} - s_{2n}\big) = 0.
$$
Therefore, \( L = M \).
4. **Conclusion:**
Since both subsequences converge to the same limit \( L \), the sequence of partial sums \( (s_n) \) converges to \( L \). That is,
$$
\sum_{n=1}^{\infty} (-1)^{n-1} a_n = L.
$$
Thus, the Leibniz criterion confirms that the alternating series converges.
---
This completes the proof.
回答:
我修改了你的提示词,它现在能正确显示格式了,但你可能会在流式传输过程中遇到一些错误 – 你可以刷新页面(F5)来获得良好的效果。 GPT-o3-mini 和 Claude 3.7 Sonnet Thinking 都支持得很好。
刷新页面后
提示词
Please use the correct **LaTeX math formula formatting in Mardown** in your responses:
1. Inline formulas: Use single dollar signs, for example $E=mc^2$
2. Display formulas: Use double dollar signs with lines break, e.g.
$$
S_{2n+1} - S_{2n} = a_{2n+1}
$$
3. Handle well error "extra open brace or missing close brace"
结果
# Proof of the Leibniz Criterion for Alternating Series
The Leibniz criterion provides conditions for the convergence of alternating series of the form $\sum_{n=1}^{\infty} (-1)^{n+1} a_n$ or $\sum_{n=1}^{\infty} (-1)^{n} a_n$.
## Theorem (Leibniz Criterion)
Let $\{a_n\}$ be a sequence satisfying:
1. $a_n > 0$ for all $n \geq 1$
2. $a_n \geq a_{n+1}$ for all $n \geq 1$ (monotonically decreasing)
3. $\lim_{n \to \infty} a_n = 0$
Then the alternating series $\sum_{n=1}^{\infty} (-1)^{n+1} a_n$ converges.
## Proof
Let's define the partial sums:
$$
S_n = \sum_{k=1}^{n} (-1)^{k+1} a_k
$$
We'll examine the behavior of even-indexed partial sums $S_{2n}$ and odd-indexed partial sums $S_{2n+1}$.
### Step 1: Show even-indexed partial sums form an increasing sequence
For consecutive even-indexed partial sums:
$$
S_{2n+2} - S_{2n} = (-1)^{2n+2+1}a_{2n+1} + (-1)^{2n+3+1}a_{2n+2} = a_{2n+1} - a_{2n+2}
$$
Since $a_{2n+1} \geq a_{2n+2}$ (by monotonicity), we have $S_{2n+2} - S_{2n} \geq 0$, meaning:
$$
S_2 \leq S_4 \leq S_6 \leq \ldots \leq S_{2n} \leq S_{2n+2} \leq \ldots
$$
### Step 2: Show odd-indexed partial sums form a decreasing sequence
Similarly, for consecutive odd-indexed partial sums:
$$
S_{2n+1} - S_{2n-1} = (-1)^{2n+1}a_{2n} + (-1)^{2n+2}a_{2n+1} = -a_{2n} + a_{2n+1}
$$
Since $a_{2n} \geq a_{2n+1}$ (by monotonicity), we have $S_{2n+1} - S_{2n-1} \leq 0$, meaning:
$$
S_1 \geq S_3 \geq S_5 \geq \ldots \geq S_{2n-1} \geq S_{2n+1} \geq \ldots
$$
### Step 3: Show even-indexed partial sums are bounded above
For any $n \geq 1$:
$$
\begin{align*}
S_{2n} &= a_1 - a_2 + a_3 - \ldots + a_{2n-1} - a_{2n} \\
&= a_1 - (a_2 - a_3) - (a_4 - a_5) - \ldots - (a_{2n-2} - a_{2n-1}) - a_{2n}
\end{align*}
$$
Since $a_k \geq a_{k+1}$ for all $k$, each term $(a_{2k} - a_{2k+1}) \geq 0$, so:
$$
S_{2n} \leq a_1
$$
### Step 4: Show odd-indexed partial sums are bounded below
Similarly, for odd-indexed partial sums:
$$
\begin{align*}
S_{2n+1} &= a_1 - a_2 + a_3 - \ldots + a_{2n-1} - a_{2n} + a_{2n+1} \\
&= a_1 - (a_2 - a_3) - (a_4 - a_5) - \ldots - (a_{2n} - a_{2n+1})
\end{align*}
$$
Each term $(a_{2k} - a_{2k+1}) \geq 0$, so:
$$
S_{2n+1} \geq a_1 - (a_2 - 0) = a_1 - a_2
$$
### Step 5: Establish convergence
Since $\{S_{2n}\}$ is increasing and bounded above, it converges to some limit $L_1$.
Since $\{S_{2n+1}\}$ is decreasing and bounded below, it converges to some limit $L_2$.
Now, we need to show $L_1 = L_2$. Observe:
$$
S_{2n+1} - S_{2n} = a_{2n+1}
$$
Taking the limit as $n \to \infty$ and using the condition $\lim_{n \to \infty} a_n = 0$:
$$
\lim_{n \to \infty} (S_{2n+1} - S_{2n}) = \lim_{n \to \infty} a_{2n+1} = 0
$$
Therefore, $L_2 - L_1 = 0$, which means $L_1 = L_2 = L$.
Since both subsequences of partial sums converge to the same limit $L$, the entire sequence $\{S_n\}$ converges to $L$, proving that the alternating series $\sum_{n=1}^{\infty} (-1)^{n+1} a_n$ converges.
### Error Bound
An additional important result is that if we approximate the sum by a partial sum $S_n$, the error is bounded by the next term:
$$
|S - S_n| \leq a_{n+1}
$$
Where $S$ is the sum of the infinite series.
This completes the proof of the Leibniz criterion. ■